Pengenalan Calistung Menggunakan Media Permainan Monopoli dengan Pendekatan Dora Eksplorer di PKBM Al Multazam Kecamatan Cimerak Kabupaten Pangandaran - Nunik Yudaningsih; Indra Nanda (Jurnal Mitra Pengabdian Farmasi, 2021)
Given the importance of education for every human being, as well as one of the steps in alleviating poverty, PKBM Multazam plays an active role in assisting government programs through the implementation of non-formal education and trying to help the illiterate community. Illiteracy is the inability to use language, the inability to read, write, count, listen and speak. This study has a goal to be achieved, namely the introduction of calistung using monopoly game media with a dora explorer approach at PKBM Al Multazam, Cimerak District, Pangandaran Regency. The research method uses descriptive, namely the method used to find the elements, characteristics, properties of a phenomenon, this method begins with collecting data, analyzing data and interpreting it. From the learning activities using monopoly media and the Dora Eksplorer approach, it can be seen clearly on the score list form with very satisfying results. This media and approach has proven to be very effective in using basic literacy groups, it is concluded that using the cooperative learning model of learning will increase the motivation and enthusiasm of learning for learning citizens. Because in this learning model, every learning citizen has the right to express his opinion and race to get the best value. This model is quite effective for developing discipline, interest, cooperation, activeness and responsibility of learning citizens because it explores the abilities of learning citizens individually even though it is carried out in groups. This learning activity is centered on learning citizens both individually and in groups so that they can find their own answers (inquiry).